The Logic Of The Pension System In Algeria - Soufi, Imane; Ghouti Belayachi, Boumediene (Recherches économiques et managériales; Vol. 21 (2017): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES, 2018)
Many questions arise: retirement, a big business? How many retirees do we count? What is the average retirement income level? Dispersion of retirees’ income? Retirement is expensive, what does this mean? And also, many suggestions: « There’s not work for everybody and workers must retire earlier and earlier » « Seniors are becoming more numerous, this is why pension costs are getting more and more expensive » « Despite their high cost pensions are too low » The article presents an insight into the old age pension system in Algeria. There are three topic paragraphs: 1. Retirement: Definition and Characteristics of Evolution, 2. The Retirement System in Algeria, 3.challenges and new reform. There, the author’s goal was to present both past and present solutions employed by the Algerian pension system, in search for ideas worth consideration, in then end the author’s present the reform in the Algerian system.   Keywords: retirement system, funding, balance of the system, demographic data. الملخص  : العديد من الأسئلة التي تطرح حول التقاعد . ايضا حول كم عدد المتقاعدين الذين يملوهم صدوق التقاعد . ما هو متوسط مستوى دخل التقاعد؟ كيف يتشتت دخل المتقاعدون؟ التقاعد مكلف، ماذا يعني هذا؟ . وأيضا، العديد من الاقتراحات « ليس هناك عمل للجميع ويجب أن يتقاعد العمال في وقت مبكر وأسبق » « أصبح عدد كبار السن أكثر عددا، وهذا هو السبب في أن تكاليف المعاشات التقاعدية تزداد وأكثر تكلفة » « على الرغم من معاشاتهم العالية التكلفة منخفضة جدا ». تقدم المقالة نظرة ثاقبة على نظام المعاشات التقاعدية للشيخوخة في الجزائر . هناك ثلاث فقرات موضوعية كالآتي : التقاعد : تعريف وخصائص التطور، 2. نظام التقاعد في الجزائر، 3. والتحديات والإصلاحات الجديدة كان هدفنا هو طرح الحلول السابقة والحالية التي يستخدمها نظام التقاعد الجزائري، بحثا عن أفكار تستحق النظر، ثم في النهاية نعرض الإصلاحات في لنظام لتقاعد الجزائري . الكلمات الرئيسية : نظام التقاعد، والتمويل، وتوازن النظام، البيانات الديموغرافية .